2001
DOI: 10.1345/aph.10368
|View full text |Cite
|
Sign up to set email alerts
|

Isotretinoin-Induced Inflammatory Bowel Disease in an Adolescent

Abstract: This case of probable isotretinoin-induced IBD suggests that patients with suspected IBD should be asked about current or past use of isotretinoin to improve documentation of this serious adverse event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…A further eight cases have been reported in the English language literature (table 1). 611 All occurred in patients without a prior diagnosis of IBD, nor symptoms to suggest underlying undiagnosed disease. In contrast to the initial reports of Brodie and Martin et al , the majority of further cases occurred shortly after cessation of isotretinoin therapy rather than whilst on treatment with the drug,411 although a delay in diagnosis of IBD in such patients cannot be excluded.…”
Section: Clinical Experiencementioning
confidence: 99%
“…A further eight cases have been reported in the English language literature (table 1). 611 All occurred in patients without a prior diagnosis of IBD, nor symptoms to suggest underlying undiagnosed disease. In contrast to the initial reports of Brodie and Martin et al , the majority of further cases occurred shortly after cessation of isotretinoin therapy rather than whilst on treatment with the drug,411 although a delay in diagnosis of IBD in such patients cannot be excluded.…”
Section: Clinical Experiencementioning
confidence: 99%
“…Although there are reports of successful Isotretinoin therapy in patients with a history of IBD, 5,6 other authors have reported cases of IBD presenting after initiation of therapy with Isotretinoin, or exacerbations of colitis after treatment with Isotretinoin. 4,[7][8][9] This case suggests that Isotretinoin may also cause an acute pan-enteritis. Given the negative family history for IBD and the strong temporal relationship between the onset of symptoms and the introduction of Isotretinoin, it is likely that Isotretinoin was the cause of the enteropathy in this patient (according to the Naranjo probability scale).…”
Section: Discussionmentioning
confidence: 81%
“…Five months after symptoms first presented, the patient required a subtotal colectomy and ileostomy. 7 Spada et al described a case of a 22-year-old man diagnosed with pan-enteritis after taking isotretinoin for 15 days. 8 The Netherlands Pharmacovigilance Centre reports three cases of inflammatory bowel disease being associated with isotretinoin between 1985 and 2005, none of which had prior histories of intestinal disease.…”
Section: Discussionmentioning
confidence: 99%